2007
DOI: 10.1186/1471-2458-7-75
|View full text |Cite
|
Sign up to set email alerts
|

A new national smokefree law increased calls to a national quitline

Abstract: BackgroundA law making all indoor workplaces including bars and restaurants smokefree became operational in New Zealand in December 2004. New Zealand has a national free-phone Quitline Service which has been operational since 1999. Previous work has shown that the number of calls to the Quitline are influenced by marketing of the service through media campaigns. We set out to investigate if the smokefree law increased calls to the Quitline.MethodsFor 24 months prior to the law, and 12 months after the law, dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 14 publications
1
14
1
Order By: Relevance
“…Furthermore, those living in the rural, distressed smoke-free community smoked approximately the same number of cigarettes per day (about 16-25 cigarettes daily during the past month) and reported about the same length of time since their last cigarette (approximately 0-7 days), compared to those living in comparable counties without smoke-free legislation. These findings are contrary to our previous study showing that smokers may be more likely to quit when living in a community with a longstanding comprehensive smoke-free workplace law (Hahn et al, 2009), and other studies reporting positive cessation outcomes after these laws (Albers et al, 2007;Gallus et al, 2006;Grassi et al, 2009;Moskowitz et al, 2000;Wilson et al, 2007).…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Furthermore, those living in the rural, distressed smoke-free community smoked approximately the same number of cigarettes per day (about 16-25 cigarettes daily during the past month) and reported about the same length of time since their last cigarette (approximately 0-7 days), compared to those living in comparable counties without smoke-free legislation. These findings are contrary to our previous study showing that smokers may be more likely to quit when living in a community with a longstanding comprehensive smoke-free workplace law (Hahn et al, 2009), and other studies reporting positive cessation outcomes after these laws (Albers et al, 2007;Gallus et al, 2006;Grassi et al, 2009;Moskowitz et al, 2000;Wilson et al, 2007).…”
Section: Discussioncontrasting
confidence: 83%
“…Some studies report increased interest in quitting, reduced consumption, and successful abstinence with smoke-free laws (Albers, Siegel, Cheng, Biener, & Rigotti, 2007;Gallus et al, 2006;Grassi, Enea, Ferketich, Lu, & Nencini, 2009;Moskowitz, Lin, & Hudes, 2000;Wilson et al, 2007), but these behaviors may be short-lived (Chan et al, 2009;Fowkes, Stewart, Fowkes, Amos, & Price, 2008;Lewis, Haw, & McNeill, 2008). One study indicated that there may be a delayed effect on cessation; the longer a comprehensive smoke-free workplace law is in place, the more likely smokers may be to quit (Hahn, Rayens, Langley, Darville, & Dignan, 2009).…”
mentioning
confidence: 90%
“…Numbers of calls remained elevated each month compared to the previous year until March 2005, and the monthly number of NRT vouchers issued was higher until May 2005 25. This pattern was observed despite a marked reduction in advertising expenditure on smoking cessation promotion in early 2005, partly implemented to reduce demand.…”
Section: Resultsmentioning
confidence: 94%
“…The main sources of information on smoking related behaviours and smoking prevalence came from time series analyses we conducted of the number of caller registrations and nicotine replacement therapy (NRT) exchange cards issued by the national quitline before and after the introduction of the smoke-free legislation25; the frequency of smoking reported by smokers in pubs and bars, restaurant and nightclubs in the HSC monitor surveys16; and from market research data from AC Nielsen on supermarket tobacco sales and Statistics New Zealand data on the amount of tobacco released onto the New Zealand market 16. We also used data on reported parental smoking prevalence among children in the national year 10 smoking survey 24…”
Section: Methodsmentioning
confidence: 99%
“…Based on studies on the effect of smoking cessation policies on quit attempts, we hypothesize that the introduction of smoke-free legislation will cause a temporary increase in search queries with a maximum duration of six months [10][11][12][13][14]. Based on findings from two RCTs and a real life study on the effects of reimbursement of SCS, it is expected that the reimbursement of SCS will cause a longer increase in search queries of maximally two years [15][16][17].…”
Section: Introductionmentioning
confidence: 99%